Mapping Post-Graduation Choice Trends: A Quantitative Study of Class XI Multimedia Students of Vocational High Schools in Sleman Regency - Nurillahi, Rico; Riyadi, Muklas (Journal of Engineering and Vocational Education, 2026)
Purpose of the study: This study aims to map the post-graduation choice tendencies of Grade XI Multimedia students at vocational high schools in Sleman Regency, focusing on their orientation toward entering the workforce or continuing their studies in higher education.Methodology: This study employed a quantitative descriptive survey design. The population consisted of 165 Grade XI Multimedia students from five vocational high schools in Sleman Regency, with 117 students selected through proportionate random sampling using the Slovin formula. Data were collected using a validated Likert-scale questionnaire and analyzed using descriptive statistics, including mean scores and percentages.Main Findings: The results show that both post-graduation tendencies are categorized as high. The tendency to continue higher education (Mean = 3.84; 76.8%) is slightly higher than the tendency to enter the workforce (Mean = 3.59; 71.8%). Internal factors, particularly personal motivation and future aspirations, were identified as the most dominant determinants influencing students’ choices. These findings indicate that students have developed relatively mature career orientations since Grade XI, with a stronger inclination toward further study.Novelty/Originality of this study: This study provides a comparative mapping of two post-graduation tendencies within the same group of Multimedia students, rather than examining employment or further study interests separately. By focusing on Grade XI students and the Multimedia specialization in Sleman Regency, this research offers contextual and updated empirical evidence regarding vocational students’ career orientation prior to graduation.